Phase I study of orally administered S-1 in combination with epirubicin and oxaliplatin in patients with advanced solid tumors and chemotherapy-naïve advanced or metastatic esophagogastric cancer - Moehler, Markus; Mahlberg, Rolf; Heinemann, Volker; Obermannová, Radka; Kubala, Eugen; Melichar, Bohuslav; Weinmann, Arndt; Scigalla, Paul; Tesařová, Marietta; Janda, Petr; Hédouin-Biville, Fabienne; Mansoor, Wasat (Gastric cancer, 2017)
BACKGROUND: This phase I study investigated the safety and the maximum tolerated dose (MTD) of the oral fluoropyrimidine S-1 when combined with epirubicin and oxaliplatin (EOS). METHODS: Patients aged ≥18 years with advanced or metastatic solid tumors were enrolled in a 3 + 3 design with S-1 dose escalation (two planned cohorts) performed according to the occurrence of dose-limiting toxicity (DLT). On day 1 of each 21-day cycle, patients received epirubicin 50 mg/m2 followed by oxaliplatin 130 mg/m2 (maximum 8 cycles) and then S-1 [20 mg/m2 (cohort 1) or 25 mg/m2 (cohort 2), twice daily]: first dose, evening of day 1; subsequent administration on days 2-14, twice daily; last dose, morning of day 15 (unlimited number of S-1 cycles). After protocol amendment, enrollment in a third cohort was restricted to patients with chemotherapy-naïve advanced or metastatic esophagogastric cancer. RESULTS: DLT was reported for two of the five patients in cohort 2, defining 20 mg/m2 twice daily as the MTD of S-1 combined with epirubicin and oxaliplatin in heavily pretreated patients. Thirteen patients with chemotherapy-naïve advanced or metastatic esophagogastric cancer were subsequently enrolled and treated at an S-1 dose level of 25 mg/m2 twice daily; no DLTs were reported; median overall survival was 13.1 months. Of the 11 evaluable patients, three (27 %) had partial responses and seven (64 %) had stable disease. The safety profile was in line with expectations. CONCLUSIONS: The promising activity of EOS (S-1 dose level, 25 mg/m2 twice daily) and acceptable safety profile support further clinical development of this combination for the first-line treatment of patients with advanced or metastatic esophagogastric cancer.
Keywords: senioři; Neoplasm Invasiveness; Stomach Neoplasms; ftorafur; First-line chemotherapy; Oxaliplatin; gastroezofageální junkce; kyselina oxonová; epirubicin; oxaliplatin; Prognosis; Epirubicin; maximální tolerovaná dávka; Middle Aged; lymfatické metastázy; mužské pohlaví; Organoplatinum Compounds; Esophagogastric Junction; aplikace orální; míra přežití; Adult; mladý dospělý; Oxonic Acid; Tegafur; Drug Combinations; fixní kombinace léků; Follow-Up Studies; Advanced gastric cancer; Lymphatic Metastasis; následné studie; Neoplasms; Neoplasm Staging; Young Adult; ženské pohlaví; prognóza; Humans; organoplatinové sloučeniny; nádory; Survival Rate; invazivní růst nádoru; Esophageal Neoplasms; lidé středního věku; S-1; Administration, Oral; Antineoplastic Combined Chemotherapy Protocols; staging nádorů; protokoly protinádorové kombinované chemoterapie; Maximum Tolerated Dose; dospělí; Female; Aged; nádory jícnu; lidé; Male; nádory žaludku